Kompetensi Dosen Era Disrupsi Industri 4.0: Bagaimana Persepsi Mahasiswa? - Annisa Diana Salsabila; Amanda Putri; Rhomiy Handican (Griya Journal of Mathematics Education and Application, 2023)
The era of technological disruption not only has an effect on changes in the business cycle, but also has an impact on the world of education. The world of education today also demands the ability to equip students with 21st century skills. These skills are the skills of learners who are able to think critically and solve problems, creatively, and innovatively, communication and collaboration skills. In the industrial era 4.0, universities are required to be able to overcome the turmoil of changes that occur due to digital transformation. Lecturers in the industrial era are required to have qualifications and competencies that can compete and survive in the turmoil of the industrial era 4.0. The purpose of this study was to determine how students perceive the competence of lecturers in the era of industrial disruption 4.0. The research method used in this research is quantitative research method with survey type. The data collection instrument used a questionnaire made through Google Forms. The sample of this study were 53 students of the Kerinci State Islamic Institute who were grouped by gender, namely 37 people (69.8%) were female and 16 people (30.2%) were male. Based on the results of the study, students were of the opinion that lecturers should be expressive and fun in teaching mathematics, lecturers should use online media to increase learning resources, lecturers should care about students and be helpful, lecturers should use language that is easy to understand, lecturers should not be rigid, lecturers should be formal and informal, lecturers should have good IT skills, lecturers in class should intersperse time with humor, lecturers should provide illustrations of theory in real and relevant forms, and ask students to use ICT in the learning process. Some of the obstacles that lecturers may face in implementing lecturer competencies in the era of industrial disruption 4.0 are lack of access and mastery of technology, lack of support from the university, and lack of awareness of the importance of lecturer competencies that are relevant to technological developments. Lecturers may also find it difficult to adapt the material taught to the rapid development of technology. To overcome these obstacles, lecturers need to be given support and training to improve their mastery of technology, as well as encouragement to continue developing their competencies.